Islamic Activism: A Social Movement Theory Approach - Quintan Wiktorowicz (Indiana Series in Middle East Studies)
This volume represents the first comprehensive attempt to incorporate the study of Islamic activism into social movement theory. It argues that the dynamics, processes, and organization of Islamic activism can be understood as important elements of contention that transcend the specificity of "Islam" as a system of meaning and identity and a basis for collective action. Drawing on extensive fieldwork, the contributors show how social movement theory can be utilized to address a wide range of questions about the mobilization of contention in support of Muslim causes. The book covers myriad examples of Islamic activism (Sunni and Shi‘a) in eight countries (Arab and non-Arab), including case studies of violence and contention, networks and alliances, and culture and framing.
Keywords: activism; Egypt; Iran; Islam; Islamic; Muslims; Shi‘a; social movement; Sunni; Yeman